Acoustic Features of Vowels in Patients with Dysarthria - Jing XU; Yalin XU; Zhiwei MOU; Jianliang LU; Chenyin JIANG (康复学报)
Dysarthria are speech disorders that result from neurologic impairments associated with weakness, slowness, or incoordination of the musculature used to produce speech. Domestic studies on this speech disorder are mostly limited to acupuncture, electrical stimulation and other therapeutic effects, and the evaluation of the therapeutic effect is mostly subjective, involving the lack of acoustic analysis. In this paper, the acoustic features of vowels with dysarthria were analyzed, such as resonant frequency, vowel space area, formant centralization ratio, vowel duration, vowel articulation index, jitter, shimmer, normalizednoise energy, standard deviation of F0, vowel dispersion, vowel overlap, vowel triangle area, acoustic distance and so on. In dysarthria, movement patterns change of articulators lead to obscure pronunciation and decline of the listening comprehension. Doctors and therapists can find the pathology differences of acoustic features between patients and normal speech and understand the internal mechanism through extracting acoustic parameters with the technique of linear predictive coding with computer. Some differences of the acoustic features of vowels with dysarthria were found compared with healthy adults. The vowel formant of the patients with dysarthria showed a centralized tendency, frequency deviation and inaccuracy (the change of frequency and amplitude was higher than that of the control group), vowel space area and vowel articulation index (VAI) were significantly reduced, and the size of vowel space was positively correlated with the speaker's understandability. The degree of vowel dispersion and overlap can indicate the severity of speech disorders. Also, the duration of vowels was longer than that of the normal control group. These abnormalities show that there are inaccuracies and abnormal movements in articulation movement in patients with dysarthria. These found of the above the acoustic features of vowels with dysarthria are conducive to the effective evaluation of clinical dysarthria through objective methods and can direct the accurate training in speech rehabilitation.